The Art of War and Peace: Understanding Our Choices in a World at War: (David Kilcullen and Greg Mills) - Jacobs, David (Scientia Militaria - South African Journal of Military Studies, 2026)
The Art of War and Peace: Understanding Our Choices in a World at War by David Kilcullen and Greg Mills, Cape Town: Random House South Africa, 2024, 320 pages, ISBN 978-1-776-39185-1.